Safeguarding Athletes' Digital Assets: Addressing Online Intellectual Property Rights in the Sports Industry's Cyber Law Void - Singh, Akriti (Trinity Law Review, 2023)
The sports industry landscape has witnessed remarkable growth, with revenue projected to surpass USD 40 billion by 2027, largely driven by advancements in technology. However, this technological progress doesn't always favor athletes, fans, and sporting organizations. Nevertheless, The era of digital transformation has created a convergence between sports and technology, opening up a plethora of opportunities for athletes to improve their performance, engage with fans, and maximize their commercial opportunities. The intersection of emerging Internet and Communication Technology within the sports industry intricately intertwines with the Sustainable Development Goals. It is incorrect to claim that there is no connection between these two subjects; in fact, their relationship is pervasive and profound. By considering the fundamental principles of Sustainable Development, we can understand Internet Governance as the decision-making process that shapes the global communication and exchange of knowledge over the internet, encompassing various aspects such as access, multi-stakeholder participation, openness, and security. These issues are equally relevant and crucial for safeguarding the rights of athletes and align with Sustainable Development Goals (SDGs) set out by the UN (United Nations). Further, Global communication and knowledge exchange play a pivotal role in providing elite sports personalities with a marketable value for their persona. The rise of the Digital era has brought about a paradigm shift in how athletes engage with their fans and capitalize on their brands even in India. Through social media platforms, online streaming services, and e-commerce channels, athletes now have unprecedented opportunities to expand their reach and monetize their image. In the context of Sustainable Development, protecting the intellectual property of the athletes deeply aligns with several SDGs.
Keywords: Safeguarding Athletes; Digital Assets; Property Rights; ports Industry's